Heavy Metals Source Apportionment and Human Health Risk Assessment of Contaminated Soils of Zamfara State, Nigeria - Sharhabil Musa Yahaya; Aliyu Ahmad Mahmud; Nafiu Abdu (Agro Bali : Agricultural Journal, 2022)
Progressive illegal artisanal mining activities threaten public health without functional law enforcement on pollution control and proper management practices. This is not an exception of Zamfara State, Nigeria, where a large portion of the populace participates in artisanal mining. The study was conducted to assess the level of health risk associated with heavy metals contaminated soils of Zamfara state, Nigeria. Soil samples were collected from five mining locations (Abare, Bagega, Dareta, Sunke, and Tungar Kudaku) and Anka-town (control site) with no record of mining activities. In each place, bulked soil samples were collected from three sites (mining site, processing site, and village), and the concentration of six heavy metals (Fe, Pb, Cd, Cr, Zn, and Ni) in all the samples were analyzed. The result of the principal component analysis and correlation analysis revealed that Pb, Zn, Cr, and Ni originated from the same source, i.e., anthropogenic/mining activities. While Fe and Cd originated from the geogenic processes because of their high abundance in the soil of the study area, as Anka-town (control site) also recorded high concentrations of Fe and Cd. Health risk assessments were carried out in two groups of population (adult and children) through three exposure pathways (i.e., ingestion, dermal contact, and inhalation). The results showed that ingestion dominated dermal contact and inhalation pathways, and Fe is the riskiest metal while Cd and Ni have the lowest risk of exposure for daily intakes. The non-cancer hazard quotient (HQ) values were all recorded below 1. For the total hazard index (THI), all the adult's exposure pathways were negligible, while for children, only Bagega has ingestion of heavy metals exceeding one (1.10), indicating that non-cancer health risks for children exist. The other four mining locations, Abare, Sunke, Tunga, and Dareta, have values approaching one (i.e., 0.71, 0.60, 0.50, and 0.74, respectively). While for Anka town, which is the control site, it has a value far less than one (0.16). These indicate that all the study locations have the potential for children's health risk through ingesting food produced from contaminated soils. Therefore, there is an urgent need to apply remediation measures immediately to combat complications raised due to heavy metal contaminations.